Soil-site suitability evaluation for mustard in calcareous soils of Girnar toposequence in Southern Saurashtra region of Gujarat (Journal of Oilseed Brassica, 2026)
The five representative pedons were evaluated for their suitability to Indian mustard [Brassica juncea (L.) Czern & Coss.] in the soils of different land slope of Girnar toposequence of Southern Saurashtra region of Gujarat. The soils of pedon P3 belong to Typic Haplustert are highly suitable for Indian mustard cultivation, whereas the soils of pedon P1 belong to Lithic Ustorthents, pedon P2 belong to Lithic Haplustepts, pedon P4 belong to Typic Haplustepts and pedon P5 belong to Typic Ustifluvents are currently not suitable for Indian mustard cultivation. Topography, shallow soil depth, high CaCO3, drainage, salinity and sodicity are the major limitations in most soils of Girnar toposequence of Southern Saurashtra. Results showed that the suitability classes can be improved if the correctable limitations (soil fertility characteristics) are altered through soil amelioration measures.